Remediation of cognitive and motor functions in Tunisian elderly patients with mild Alzheimer’s disease: implications of music therapy and/or physical rehabilitation - Sarah Chéour; Chouaieb Chéour; Tommy Gendreau; Majdi Bouazizi; Kumar Purnendu Singh; Ayoub Saeidi; Dan Tao; Rashmi Supriya; Nicola Luigi Bragazzi; Julien S. Baker; Foued Chéour (Frontiers in Aging Neuroscience, 2023)
The purpose of this study was to compare the effects of music therapy (MT) and/or physical rehabilitation (PR) on cognitive and motor function in elderly Tunisian male and female patients with mild Alzheimer’s disease (AD). Male patients (N: 16; age: 74.19 ± 4.27 years; weight: 76.71 ± 5.22 kg) and female patients (N: 12; age: 71.46 ± 3.36 years; weight: 67.47 ± 4.31 kg) with mild AD were randomly assigned into 4 groups including control group (Co), PR group participated in physical rehabilitation, MT group received music therapy and MT + PR received both music therapy and physical rehabilitation. Participants were required to engage in the study for four months with three 60-min sessions per week. We found all scores of cognitive (MMSE, ADAS-Cog Total and the ADAS-Cog Memory subscale) and motor functions (step length, walking speed, 6MVT and BBS score) evaluated were the greatest in MT + PR compared to the other groups. Our study also demonstrated that MT has a greater effect on cognitive function, while PR has a more pronounced effect on motor function. Changes in MMSE scores were significantly positively correlated in the PR, MT and MT + PR groups with improvements in all motor functions including step length (r = 0.77), walking speed (r = 0.73), 6MVT (r = 0.75) and BBS scores (r = 0.78) in AD patients. In conclusion, the combination of MT and PR seems to be an appropriate intervention approach that needs consideration as a treatment strategy for elderly male and female patients with mild AD.